2008
DOI: 10.1016/j.nima.2008.07.035
|View full text |Cite
|
Sign up to set email alerts
|

Advances in gaseous photomultipliers

Abstract: We review latest progress in gaseous photomultipliers (GPM) combining solid photocathodes and various types of novel electron multipliers. Cascaded gaseous electron multipliers (GEM) coated with CsI photocathodes can efficiently replace UVsensitive wire chambers for single-photon recording in Cherenkov and other detectors. Other hole-multipliers with patterned electrodes (Micro-Hole and Strip Plates) and improved ion-blocking properties are discussed; these permit reducing considerably photon-and ion-induced s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(73 citation statements)
references
References 87 publications
(61 reference statements)
0
73
0
Order By: Relevance
“…Applications of PSGPMs were widely extended (see review paper [18]]) when solid photo cathodes, in particular made of CsI, were combined with another gas multiplication structure called -hole-type‖ [19][20][21]. In a few words, the modern hole-type detector is a dielectric sheet metalized on both sides in which an array of holes is created by a chemical etching technique or by mechanical drilling (see Fig.…”
Section: Hole-type Uv Sensitive Psgpmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Applications of PSGPMs were widely extended (see review paper [18]]) when solid photo cathodes, in particular made of CsI, were combined with another gas multiplication structure called -hole-type‖ [19][20][21]. In a few words, the modern hole-type detector is a dielectric sheet metalized on both sides in which an array of holes is created by a chemical etching technique or by mechanical drilling (see Fig.…”
Section: Hole-type Uv Sensitive Psgpmsmentioning
confidence: 99%
“…During the last decade or so there have been a lot of efforts in the development of gaseous detectors sensitive to visible light (see review papers [33,34]. The experience of several groups have however shown that it is not an easy task to employ solid photocathodes sensitive to visible light (SbCs, GaAs/Cs or bialkaline) in an ordinary gas amplification structure, such as wire chambers or parallel-plate chambers (PPAC) [22,35] There are two main problems: 1) any tiny trace of impurities (for example, oxygen or water) cause degradation of the photocathode quantum efficiency due the photocathode destruction 2) in presence of high quantum efficiency photocathodes, it is almost impossible to reach gains above 10-100 due to the photon and ion feedback.…”
Section: Gaseous Detectors With Solid Photocathodes Sensitive To Visimentioning
confidence: 99%
“…These scintillators can be coupled with the detectors filled with photosensitive gases such as tetrakis dimethylamine ethylene (TMAE) or triethylamine (TEA) or to the other VUV-sensitive detectors for example a photomultiplier with CsI photocathode (Schotanus et al, 1989;Chechik and Breskin, 2008). One of the promising candidates for the VUV scintillators can be for example the Nd-doped LaF 3 or BaY 2 F 8 (BaYF).…”
Section: Introductionmentioning
confidence: 99%
“…ese can be used to create large area detectors. Breskin et al work on such detectors coupled to photocathodes to create large area detectors capable of detecting single photons [42,43,44]. Many more variants of GEM detectors exist.…”
Section: Gem Detectorsmentioning
confidence: 99%
“…e photosensitivity is obtained by coating the grid with a re ective CsI photocathode [112]. CsI is a very robust photocathode that has been used in combination with many gaseous photon detectors [44]. In [113] a Micromegas device with a single anode is coupled to a CsI re ective photocathode.…”
Section: E Detector Systemmentioning
confidence: 99%